Adriaan Martens en Henry Van De Velde : geneeskunst aan de Leie - Vandeputte, Benoît; Van Moerbeke, Katrien; Puype, Karel (Oostkamp: Stichting Kunstboek, 2018)
"Benoît Vandeputte ; eindredactie: Katrien Van Moerbeke, Karel Puype"